Development of Care Model for Type 2 Diabetic Patients by Multidisciplinary Team with Family Medicine Principles - Saisawan, Thaworn (Journal of Health Science of Thailand, 2020)
This study was a quasi-experimental research with an objective to compare the knowledge of type 2 diabetic patients on diabetes, the self-care behaviors and HbA1c before and after applying a care model by multidisciplinary team with family medicine principles. The samples were selected by the purposive sampling technique to include the patients with type 2 diabetes mellitus attending Khao Tha Phra health promotion hospital, Muang district, Chainat province. They were divided into two groups: the control (32 patients) who received routine diabetic care and the experimental group (32 patients) who received medical services based on the care model with family medicine principles, provided by a multidisciplinary team. Data were collected using the questionnaire to assess knowledge of diabetes, the self-care behaviors and the HbA1c record. Data were analyzed by frequency, percentage, mean, standard deviation, and paired t-test. The results of this study showed that (1) the experimental group’s mean score of the knowledge of diabetes and the self-care behaviors were significantly higher than before the program; and significantly higher than those of the control group (p<0.01); (2) the experimental group’s mean score of the HbA1c was significantly lower than before the program; and significantly lower than that of the control group (p<0. 01).